DISINFORMATION AND DIGITAL ELECTORAL CRIMES: CHALLENGES FOR DEMOCRACY (CIPEEX, 2025)
This study analyzes the impacts of disinformation and digital electoral crimes on the Brazilian democratic process, highlighting the challenges faced by the Electoral Justice and civil society, as well as the measures required to strengthen the integrity of elections in the twenty-first century. It adopts a bibliographic and documentary approach based on current legislation, reports, and programs of the Superior Electoral Court (TSE), in addition to academic works addressing disinformation, digital communication, and democracy. The results demonstrate that, within the electoral context, disinformation undermines essential democratic principles such as freedom of choice, equality among candidates, and transparency of the electoral process. The most recurrent forms include fake news, deepfakes, manipulation of images and videos, and the massive use of social networks and messaging applications for the rapid dissemination of misleading content. At the same time, the practice of digital electoral crimes—such as hacking systems, leaking personal data, misusing algorithms for illegitimate segmentation of voters, and using bots and fake profiles to artificially amplify campaigns—threatens both the fairness of elections and public trust in democracy. In response, the TSE has implemented programs to combat disinformation, expanded cooperation with digital platforms, and developed monitoring systems for suspicious content. However, persistent challenges remain, including adequate regulation of platforms, accountability for authors and disseminators of false content, protection of freedom of expression, and the urgent need to address impunity in the digital environment. Another crucial result concerns the role of media literacy: in an increasingly connected society, the development of critical and conscious citizens is indispensable. Combating disinformation cannot be limited to institutional initiatives; it requires the engagement of civil society, digital platforms, and voters themselves. The study concludes that Brazilian democracy is at a decisive moment of adaptation to new technologies. The spread of disinformation and the practice of digital electoral crimes distort truth and undermine public trust in democratic institutions. Effective solutions demand strengthened cooperation among the State, digital platforms, and civil society, combined with robust media education that empowers citizens to identify and reject false content, thereby advancing toward more transparent, secure, and legitimate elections.
Keywords: disinformation; digital electoral crimes; democracy; media literacy